PENGARUH TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK - Ermawati Arief, Yondra Syukri Ramadhan, Yasnur Asri, (Universitas Negeri Padang, 2017)
The aim of this research is to analyze the effect of implementation mind mapping techniques toward writing exposition skill ten grade students of SMA Negeri 1 Solok District Subdistrict Gumanti Fistula. This research is quantitative research with experiment method and used the one group pretest-postest design. The research population and sample was the eight grade students of SMA Negeri 1 SolokDistrict Subdistrict Gumanti Fistula in the academic year 2016/2017. The samplingtechnique usedispurposive sampling, the obtainable based on the sampling technique are X.1 class as sample of this research. The result of this research is there was a significant effect of the implementation of mind mapping techniques toward writing exposition skill ten grade students of SMA Negeri 1Solok District Subdistrict Gumanti Fistula by freedom degree n-2 with significants rate 95% and tobservationÂ isbiggerthanttabel thatis6,40>1,70. It means, mind mapping techniques was effective use in writing eksposition of observation skill ten grade students of SMA Negeri 1Solok District Subdistrict Gumanti Fistula . Observe the benefit and effectiveness of mind mapping techniques, it proved that mind mapping techniques can use as reference and developing of inovation toward writing a script drama one round skill.Â Kata kunci: Â pengaruh, mind mapping, teks eksposisi